Takayasu Arteritis With Extensive Cardiovascular, Neurovascular, and Mesenteric Involvement - Custer, Adam (JACC Case Rep, 2020)
Takayasu arteritis is a rare large vessel vasculitis with an incidence of 1 to 3 per million. This disease typically involves the aorta and its primary branches but has been found to involve the coronary arteries in 7% to 9% of cases. We highlight the need for prompt diagnosis and treatment. (Level of Difficulty: Beginner.)